Analysis of Food Inflation in Java and Sumatra Islands - Na Nairobi; Laura Caroline (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
The purpose of this study is to analyze the factors of food inflation in Java and Sumatra. This study uses Panel Data regression analysis to identify inflation and uses a panel data model from 2013 - 2019 with a sample of 16 provinces in Sumatra and Java, to determine the effect of each variable on the Consumer Price Index. The results of this study indicate that from the panel data regression analysis that the independent variables of the World Food Price Index, the Average Price of Onions, Rice, Chili and Chicken in the Provincial Capital have an effect on the Consumer Price Index, while Per Capita PDRB does not have a significant effect on the Consumer Price Index in the Province. Java and Sumatra.